Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations woman who is married at 5th July 1948 to a man who is insured under the existing Scheme of Contributory Pensions will usually on his death qualify, according to her circumstances, for a Widow's or Widowed Mother's Allowance or a Widow's Pension under the new Scheme, or, failing these, for a 10s. pension as under the present Scheme. GUARDIAN'S ALLOWANCE 37. If both parents of a child are dead, and one at least of them was insured, anyone who has the child in his family will qualify for a Guardian's Allowance at the rate of 12s. a week, but not for a Family Allowance. There are no conditions, except that the child must be in the family of the guardian and must be under school leaving age. From 5th July 1948 the Guardian's Allowance of 12s. a week will take the place of the Orphan's Pension of 7s. 6d. a week under the present Scheme if the orphan is in a family. RETIREMENT PENSION 38. Who are Qualified? An insured man aged 65 or over, or an insured woman aged 60 or over, who has retired from regular employment and who satisfies the conditions explained below, may qualify for a Retirement Pension. The wife of a retirement pensioner, even though she is not herself insured, may qualify for a pension of her own at age 60 provided that she is retired. 39. What are the Rates of Pension? The standard weekly rate of Retirement Pension is 26s. ; for a married woman whose title depends on her husband's insurance the rate is 16s., raised to 26s. if she becomes a widow. An increase of 16s. is payable to a retirement pensioner if he has a dependent wife under 60 ; and 7s. 6d. for one child under school-leaving age. 23 345/3/2/10